A comparison of the efficacy of metacognitive therapy, solution-focused therapy and endurance exercises on self-efficacy beliefs of female students with social phobia disorder - Elahe Bagheri; Kourosh Goodarzi; Mehdi Roozbahani; Keivan Kakabraee (مجله علوم روانشناختی)
Background: One of the most common disorders that negatively impacts all aspects of individuals' lives is social phobia disorder. In recent decades, there has been an increasing trend towards investigating the effectiveness of new therapeutic approaches in reducing social anxiety disorder among adolescents, and treatment protocols such as endurance training, metacognitive therapy, and solution-focused therapy have been examined for their efficacy in various studies. However, a research gap exists as no study has focused on comparing the differences between these treatments. Aims: The aim of the present study was to compare the effectiveness of metacognitive therapy, solution-focused therapy, and endurance training on self-efficacy beliefs of female students with social anxiety disorder. Methods: The present study employed a quasi-experimental design with pre-test, post-test, and one-month follow-up. Sixty female students from the second grade of secondary school in three educational districts of Kermanshah city in the academic year 1401-1402 were selected as the research sample based on accessibility and inclusion criteria. They were randomly assigned to four groups of 15 (three experimental and one control). The research instruments included the Social Anxiety Scale (Connor, 2000) and General Self-Efficacy Scale (Sherer, 1982). The data were analyzed using SPSS23 software and mixed analysis of variance. Results: The findings indicated that all three treatments led to an increase in self-efficacy beliefs of students with social anxiety disorder (p< 0.05), and no significant differences in effectiveness were observed among the three intervention groups of metacognitive therapy, solution-focused therapy, and endurance training (p> 0.05). Conclusion: Given that metacognitive therapy, solution-focused therapy, and endurance training were effective in enhancing self-efficacy beliefs of individuals with social anxiety disorder, it is recommended to utilize these two approaches to reduce social anxiety symptoms and improve the quality of life and other problems in private counseling centers.